2014
DOI: 10.1371/journal.pone.0109055
|View full text |Cite
|
Sign up to set email alerts
|

The Indolinone MAZ51 Induces Cell Rounding and G2/M Cell Cycle Arrest in Glioma Cells without the Inhibition of VEGFR-3 Phosphorylation: Involvement of the RhoA and Akt/GSK3β Signaling Pathways

Abstract: MAZ51 is an indolinone-based molecule originally synthesized as a selective inhibitor of vascular endothelial growth factor receptor (VEGFR)-3 tyrosine kinase. This study shows that exposure of two glioma cell lines, rat C6 and human U251MG, to MAZ51 caused dramatic shape changes, including the retraction of cellular protrusions and cell rounding. These changes were caused by the clustering and aggregation of actin filaments and microtubules. MAZ51 also induced G2/M phase cell cycle arrest. This led to an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Akt phosphorylation has previously been reported to inhibit the activity of GSK-3β, which is an important downstream target protein of Akt (20). These results are consistent with previous studies, which reported on the function of Akt/GSK-3β in glioma (21,22). In addition, a large number of lncRNAs have been reported to regulate human cancers via actions on the Akt/GSK-3β pathway.…”
Section: Discussionsupporting
confidence: 94%
“…Akt phosphorylation has previously been reported to inhibit the activity of GSK-3β, which is an important downstream target protein of Akt (20). These results are consistent with previous studies, which reported on the function of Akt/GSK-3β in glioma (21,22). In addition, a large number of lncRNAs have been reported to regulate human cancers via actions on the Akt/GSK-3β pathway.…”
Section: Discussionsupporting
confidence: 94%
“…S1). The specificity for VEGFR-3 has been described in detail in our previous study , and was also confirmed by the significant decrease in VEGFR-3 protein levels in VEGFR-3-silenced C6 cells using small interfering RNA transfection (Park et al 2014; Supplementary Fig. S2).…”
Section: Tissue Processing and Immunohistochemistrysupporting
confidence: 81%
“…Cell cycle disorders such as phase arrest might be an important cause of inhibition of cancer cell growth and consequently the loss of cell viability [ 41 ]. Previous research showed that many drugs induced cell cycle arrest at the G2/M phase in cancer cells [ 42 ]. To reveal the mechanism behind the inhibitory effect of the synthesized compounds on cellular viability, we sought to examine the cell cycle regulation.…”
Section: Resultsmentioning
confidence: 99%